2016
DOI: 10.1073/pnas.1517558113
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting variability patterns in the default mode and sensorimotor networks balance in bipolar depression and mania

Abstract: Depressive and manic phases in bipolar disorder show opposite constellations of affective, cognitive, and psychomotor symptoms. At a neural level, these may be related to topographical disbalance between large-scale networks, such as the default mode network (DMN) and sensorimotor network (SMN). We investigated topographical patterns of variability in the resting-state signal-measured by fractional SD (fSD) of the BOLD signal-of the DMN and SMN (and other networks) in two frequency bands (Slow5 and Slow4) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
141
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(171 citation statements)
references
References 90 publications
13
141
8
Order By: Relevance
“…Reduction in the integrative role of the hippocampus and vmPFC likely leads to impairment in stimuli appraisal and in selecting contextually appropriate responses. Moreover, the reduction of the integrative role of the default-mode network, when considered together with the findings of the sensorimotor network dysconnectivity described above, supports the study by Martino and colleagues (2). They found that the balance between the default-mode and sensorimotor networks activity patterns was altered during acute episodes, favoring the default-mode network in depression and the sensorimotor network in mania.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Reduction in the integrative role of the hippocampus and vmPFC likely leads to impairment in stimuli appraisal and in selecting contextually appropriate responses. Moreover, the reduction of the integrative role of the default-mode network, when considered together with the findings of the sensorimotor network dysconnectivity described above, supports the study by Martino and colleagues (2). They found that the balance between the default-mode and sensorimotor networks activity patterns was altered during acute episodes, favoring the default-mode network in depression and the sensorimotor network in mania.…”
Section: Discussionsupporting
confidence: 89%
“…Resting-state functional magnetic resonance (rs-fMRI) studies in BD have shown disease mechanisms influence intrinsic connectivity including that of the default-mode, sensorimotor and central executive networks (13). Imbalance between the functional connectivity of the sensorimotor and default-mode networks has been directly linked with the clinical expression of bipolar disorder, as illustrated in a recent study that found the sensorimotor and default-mode networks showing opposite variability patterns during depressive and manic episodes (2). …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly what we observe in HC is in line with results of our prior work on BD where we found a shift of the DMN/SMN fSD balance towards the SMN in mania and the opposite in depression (Martino et al, ). Psychomotricity in mania is usually described as increased, unstable, and influenced by external stimuli (as manifested in symptoms like hyperactivity and distractibility).…”
Section: Discussionsupporting
confidence: 93%
“…These regions are recruited during autobiographical memory, associative memory, semantic and conceptual knowledge, and spatial information that may be associated with altered "disturbed relatedness" factor as well as with the cognitive alterations of BPD (Ruocco, 2005). Altered engagement of the DMN has been reported not only in BPD (Wolf et al, 2011), but also in depression (Sambataro et al, 2014), bipolar disorders (Martino et al, 2016), and schizophrenia (Sambataro et al, 2010) that are disorders with clinical similarities with BPD.…”
Section: Introductionmentioning
confidence: 99%